Ethics of Care about Social Change and Its Application in the Foundations of Public Policy in Indonesia - Ma'rief, Muammar Iqbal (Universitas Kadiri, 2025)
Social change in Indonesia presents complex humanitarian challenges, ranging from natural disasters and migration to structural poverty. This situation demands public policies that not only emphasize administrative effectiveness but also take ethical dimensions into account. This article aims to analyze social change from the perspective of the ethics of care and examine how this ethical framework can be applied as a foundation for public policy formulation. The research method employed is qualitative-analytical with a literature study approach, through a critical review of policy documents, government reports, and relevant academic literature. The analysis shows that Indonesian public policies often remain technocratic and procedural, as seen in delayed disaster relief, misdirected COVID-19 cash assistance, and the digital gap in the Pre-Employment Card Program. Integrating care principles empathy, relational responsibility, and attentiveness to vulnerability can enhance legitimacy and effectiveness in public policy. This article recommends adopting the ethics of care as an alternative paradigm in public administration so that social change can be managed in a more humane, just, and sustainable manner.